(untitled) (diségno, 2022)
Modern archives are a precious source for investigating not only the evolution with which the language of drawing has accompanied and narrated the architectural project at a particular moment in its history, but, especially when referred to the horizon of unbuilt works, they also represent an extraordinary tool for interpreting the sometimes unexpressed potential or urban utopias that marked the evolution of thought on the city in the 20th century. Valuable evidence of this is provided by the drawings kept in Frediano Frediani’s private archive, which tell of the urban utopia of an unprecedented Naples, extremely avant-garde and at the same time deeply rooted in its territorial identity. In the abundant archive material, the aim is to investigate some of Frediani’s unrealised architectures, in which the author proposes waterfront solutions that tell of the relationship of the Campania capital with the sea, and which are inserted along a stretch of coastline central to everyday urban dynamics.